Total Global Strategy / Managing for Worldwide Competitive Advantage - Yip S. George (Prentice Hall, 1995)
This book offers managers and aspiring managers a systematic integration of many of the ideas surrounding global strategy. Preface, Understanding Global Strategy, Diagnosing Industry Globalization Potential, Building Global Market Participation, Designing Global Products and Services, Locating Global Activities, Creating Global Marketing, Making Global Competitive Moves, Building the Global Organization, Measuring Industry Drivers and Strategy Levers, Conducting a Global Strategy Analysis, Worksheets for Evaluating Core Strategy, Bibliography, Index.